Optimal Design of Asynchronous Motor based on Finite Element Simulation - Cao, Yongkang (Transactions on Computer Science and Intelligent Systems Research, 2023)
Aiming at motors’ deficiencies such as short life, low efficiency, and high cost in China, this paper optimizes the design of asynchronous motors, so as to improve its performance and efficiency, prolong its life, and reduce its cost. Simulating an asynchronous motor by Maxwell, a finite element simulation software, this paper analyzes the distribution diagrams of waveform and magnetic field including its voltage, current, torque, and back electromotive force to verify the design reliability. Moreover, the parametric simulation of the motor is implemented through the function of Maxwell parameter solver, and the electromagnetic performance under different initial design parameters is simulated. Then, a sensitivity analysis algorithm is adopted to analyze the sensitivity of the motors’ initial design parameters. Meanwhile, this paper establishes the platform of motor optimization design, through which the optimization design of motors with different specifications can be fulfilled.